Booster vaccination is required to elicit and maintain COVID-19 vaccine-induced immunity in SIV-infected macaques. Issue 1 (31st December 2023) - Li, Pingchao; Wang, Qian; He, Yizi; Yang, Chenchen; Zhang, Zhengyuan; Liu, Zijian; Liu, Bo; Yin, Li; Cui, Yilan; Hu, Peiyu; Liu, Yichu; Zheng, Pingqian; et al.
ABSTRACT : Prolonged infection and possible evolution of SARS-CoV-2 in patients living with uncontrolled HIV-1 infection highlight the importance of an effective vaccination regimen, yet the immunogenicity of COVID-19 vaccines and predictive immune biomarkers have not been well investigated. Herein, we report that the magnitude and persistence of antibody and cell-mediated immunity (CMI) elicited by an Ad5-vectored COVID-19 vaccine are impaired in SIV-infected macaques with high viral loads (> 10 5 genome copies per ml plasma, SIV hi ) but not in macaques with low viral loads (< 10 5, SIV low ). After a second vaccination, the immune responses are robustly enhanced in all uninfected and SIV low macaques. These responses also show a moderate increase in 70% SIV hi macaques but decline sharply soon after. Further analysis reveals that decreased antibody and CMI responses are associated with reduced circulating follicular helper T cell (TFH) counts and aberrant CD4/CD8 ratios, respectively, indicating that dysregulation of CD4 + T cells by SIV infection impairs the COVID-19 vaccine-induced immunity. Ad5-vectored COVID-19 vaccine shows no impact on SIV loads or SIV-specific CMI responses. Our study underscores the necessity of frequent booster vaccinations in HIV-infected patients and provides indicative biomarkers for predicting vaccination effectiveness in these patients.